Estrategias de competitividad turística para la comercialización y posicionamiento de productos culturales del cantón Montecristi en el contexto del COVID – 19 - Cabrera Cueva, Richard Polivio (2023)
The purpose of this research was to develop tourism competitiveness strategies for the commercialization and positioning of cultural products in Montecristi canton. The methodology is exploratory-descriptive with a quantitative and qualitative approach. In the first phase, the current conditions of the study area were determined through a bibliographic/documentary review, the stakeholder matrix, and the tourist profile matrix. In the second phase, the tourism potential of the canton was evaluated through the SECTUR files, potentialities matrix, competitive profile matrix, EFI, EFE, SWOT. In the third phase, the structure of tourism competitiveness strategies was developed through brainstorming and the 5W2H matrix. This research had as results, that despite the cultural richness of the canton, tourism is not one of the main economic activities, being trade the predominant activity; on the other hand, it was identified that the canton has existing cultural attractions with potential for tourism development in Montecristi, however, it requires the improvement of other components of the tourism system. In spite of this, the non-existence of established cultural tourism products was evidenced, for this reason a cultural tourism route was proposed in this research. Therefore, six tourism competitiveness strategies were designed with actions aimed at the creation of new tourism products and services, promotion, marketing and positioning, tourism management, quality of services, in order to generate a better functioning and tourism development of the territory.